Characterization and mechanism of action of amphibian-derived wound-healing-promoting peptides - Wang, Xiakun; Duan, Hongcheng; Li, Min; Xu, Wei; Wei, Lin (Frontiers in Cell and Developmental Biology, 2023)
Wound healing-promoting peptides are excellent candidates for developing wound healing agents due to the small size and low production cost. Amphibian is one of the major sources of bioactive peptides, including wound healing-promoting peptides. So far, a series of wound healing-promoting peptides were characterized from amphibians. We hereby summarized the amphibian-derived wound healing-promoting peptides and their mechanism of action. Among these peptides, two peptide (tylotoin, TK-CATH) was characterized from salamander, and twenty five peptides were characterized from frogs. These peptides generally have small sizes with 5-80 amino acid residues, nine peptides (tiger 17, cathelicidin-NV, cathelicidin-DM, OM-LV20, brevinin-2Ta, brevinin-2PN, tylotoin, Bv8-AJ, RL-QN15) have intramolecular disulfide bond(s), seven peptides (temporins A, temporins B, esculentin-1a, tiger 17, Pse-T2, DMS-PS2, FW-1, FW-2) are amidated at C-terminus, and the others are linear peptides without modifications. They all efficiently accelerated the healing of skin wound or photodamage in mice or rats. They selectively promoted the proliferation and migration of keratinocytes and fibroblasts, recruited neutrophils and macrophages to wounds, and regulated the immune response of neutrophils and macrophages in wounds, which were essential for wound healing. Interestingly, MSI-1, Pse-T2, cathelicidin-DM, brevinin-2Ta, brevinin-2PN and DMS-PS2 were just antimicrobial peptides, but they also significantly promoted the healing of infected wound by clearing off bacteria. Considering the small size, high efficiency and definite mechanism, amphibian-derived wound healing-promoting peptides might be excellent candidates for developing novel wound healing-promoting agents in future.